2006
DOI: 10.1002/mabi.200600017
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Membranes Electrospinning from Acrylonitrile‐Based Polymers: Specific Absorption Behaviors and States of Water

Abstract: Fibrous membranes with a fiber diameter ranging from 80 to 800 nm are prepared from polyacrylonitrile and poly[acrylonitrile-co-(N-vinyl-2-pyrrolidone)] by the electrospinning process. The parameters can be controlled to fabricate fibrous membranes with similar fiber diameters (between 600 and 800 nm) for further studies on the swelling behaviors and water states. Water swelling experiments indicate that the fibrous membrane has a great capacity for water sorption, which reaches a maximum in a few minutes beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…With our optimized electrospinning parameters reported previously, 31 beads-free and relatively uniform nanofibers were electrospun onto polymerdense membranes to create nanostructured surfaces. The electrospinning process is schematically illustrated in Figure 1.…”
Section: Fabrication Of Model Surfaces Covered With Random or Alignedmentioning
confidence: 99%
See 1 more Smart Citation
“…With our optimized electrospinning parameters reported previously, 31 beads-free and relatively uniform nanofibers were electrospun onto polymerdense membranes to create nanostructured surfaces. The electrospinning process is schematically illustrated in Figure 1.…”
Section: Fabrication Of Model Surfaces Covered With Random or Alignedmentioning
confidence: 99%
“…Both polyacrylonitrile (PAN) with relatively poor biocompatibility and poly[acrylonitrile-co-(N-vinyl-2pyrrolidone)] (PANCNVP) with excellent biocompatibility were used for preparing nanofiber or underlying membrane. 31,32 In view of the fact that blood platelets play a crucial role in coagulation and that platelets adhesion has been generally applied to evaluate the hemocompatibility of materials, the adhesion of blood platelets on the resultant nanostructured surfaces was carefully studied. It was found that the generation of nanofibers on polymer surface could greatly promote the adhesion of blood platelets.…”
Section: Introductionmentioning
confidence: 99%
“…With our optimized electrospinning parameters reported previously,31 beads‐free and relatively uniform nanofibers were electrospun onto polymer‐dense membranes to create nanostructured surfaces. The electrospinning process is schematically illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, surfaces with random or aligned nanofibers were successfully created on versatile polymer membranes by electrospinning technique. Both polyacrylonitrile (PAN) with relatively poor biocompatibility and poly[acrylonitrile‐ co ‐( N ‐vinyl‐2‐pyrrolidone)] (PANCNVP) with excellent biocompatibility were used for preparing nanofiber or underlying membrane 31, 32. In view of the fact that blood platelets play a crucial role in coagulation and that platelets adhesion has been generally applied to evaluate the hemocompatibility of materials, the adhesion of blood platelets on the resultant nanostructured surfaces was carefully studied.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been shown to fabricate scaffolds to membranes as a function of the substrate exposure time to the threading process. 36,37 The essential difference between the ability for forming fibers via electrosprays to electrospinning is that the former has the ability to locate the fibers in selected areas on a substrate while the latter has no control. However the latter has been shown to form controlled fiber orientated structures 38 which are of most interest for a range of applications where for example living cells could be encouraged to proliferate along the fiber in a controlled direction.…”
Section: Electrospinning (Es)mentioning
confidence: 99%